2018
DOI: 10.4066/biomedicalresearch.29-18-926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bilateral and unilateral caloric vestibular stimulation in scopolamine induced dementia in Wistar albino rats

Abstract: This study was undertaken to provide preliminary evidence for beneficial effects of both bilateral as well as unilateral caloric vestibular stimulation as an alternative therapy for enhancement of cognition and motor activity in Scopolamine induced dementia in Wistar albino rats. 36 healthy, adult male Wistar albino rats with body weight ranging from 150-200 g were used in the current study. Donepezil is used as standard drug in this study. Donepezil was administered orally at a dose of 5 mg/kg for 14 days. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…CVS has also been used in biomedical engineering research to investigate fluid dynamic properties of the endolymph and semi-circular canal structures (Kassemi et al, 2005;Kassemi et al, 2004;Meiry & Young, 1967;Rabbitt, 2019;Santos et al, 2017;Steer, 1967;Wu et al, 2021). CVS has been used as an intervention for psychiatric disorders such as schizophrenia, psychosis, psychopathy (Jones & Pivik, 1985;Levy et al, 1983), has been shown to temporarily reduce spatial hemi-neglect in patients with brain injury, reduce symptoms of dementia in mice and pain in humans (Ferrè et al, 2015;Jinu et al, 2018;Moon et al, 2006). Behavioural studies have shown that individuals with impaired vestibular function are unable to accurately update their perceived position in space during CVS and real self-rotation when visual cues are not present (Karnath, 1994;Metcalfe & Gresty, 1992;Panichi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CVS has also been used in biomedical engineering research to investigate fluid dynamic properties of the endolymph and semi-circular canal structures (Kassemi et al, 2005;Kassemi et al, 2004;Meiry & Young, 1967;Rabbitt, 2019;Santos et al, 2017;Steer, 1967;Wu et al, 2021). CVS has been used as an intervention for psychiatric disorders such as schizophrenia, psychosis, psychopathy (Jones & Pivik, 1985;Levy et al, 1983), has been shown to temporarily reduce spatial hemi-neglect in patients with brain injury, reduce symptoms of dementia in mice and pain in humans (Ferrè et al, 2015;Jinu et al, 2018;Moon et al, 2006). Behavioural studies have shown that individuals with impaired vestibular function are unable to accurately update their perceived position in space during CVS and real self-rotation when visual cues are not present (Karnath, 1994;Metcalfe & Gresty, 1992;Panichi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%